Field Screening of Wheat Advanced Lines for Salinity Tolerance - Ehab S. A. Moustafa; Mohamed M. A. Ali; Mohamed M. Kamara; Mohamed F. Awad; Abdallah A. Hassanin; Elsayed Mansour (Agronomy, 2021)
Salinity in soil or irrigation water requires developing genetically salt-tolerant genotypes, especially in arid regions. Developing salt-tolerant and high-yielding wheat genotypes has become more urgent in particular with continuing global population growth and abrupt climate changes. The current study aimed at investigating the genetic variability of new breeding lines in three advanced generations F6–F8 under salinity stress. The evaluated advanced lines were derived through accurate pedigree selection under actual saline field conditions (7.74 dS/m) and using saline water in irrigation (8.35 dS/m). Ninety-four F6 lines were evaluated in 2017–2018 and reduced by selection to thirty-seven F7 lines in 2018–2019 and afterward to thirty-four F8 lines in 2019–2020 based on grain yield and related traits compared with adopted check cultivars. Significant genetic variability was detected for all evaluated agronomic traits across generations in the salt-stressed field. The elite F8 breeding lines displayed higher performance than the adopted check cultivars. These lines were classified based on yield index into four groups using hierarchical clustering ranging from highly salt-tolerant to slightly salt-tolerant genotypes, which efficiently enhance the narrow genetic pool of salt-tolerance. The detected response to selection and high to intermediate broad-sense heritability for measured traits displayed their potentiality to be utilized through advanced generations under salinity stress for identifying salt-tolerant breeding lines.